Institutional balance and imbalance within the debate of new institutionalism in political science: stagnation and path change - Silva, Ivan Henrique de Mattos (Faculdade de Ciências e Letras - Unesp - Araraquara., 2016)
The study of Politics went through several changes, slowly moving away from the Political Philosophy and Sociology, and, more recently, affirming itself as an autonomous branch of knowledge. The focus on institutions has played a central role in this process, and it assumes a privileged position in the current debate of Political Science, even though there are many approaches and ways to instrumentalize them as objects of study. The goal of this paper is to accomplish a brief discussion about the relationship between institutional balance and imbalance (or, in other words, stagnation and institutional change) within new institutionalism through the discussion of certain fundamental authors.